The ANALYSIS OF THE BEHAVIOR OF NEW VOTERS IN THE 2024 REGIONAL ELECTIONS AT GKPI PADANG BULAN SENIOR HIGH SCHOOL, MEDAN BARU DISTRICT, MEDAN CITY - HARAHAP, PUTRA PRATAMA; EUNIKE BR SIMANJUNTAK; GABRIELLA STEPANI; NURUL FEBRIYANI HARAHAP; HALKING (UIN Mataram, 2024)
This study aims to analyze the behavior of new voters in the 2024 regional elections at GKPI Padang Bulan Private High School. Using a descriptive qualitative approach, this study describes the phenomenon of the behavior of GKPI Padang Bulan Private High School students in choosing their chosen leaders. Data collection was carried out through observation, interviews, and documentation. The results of observations, interviews, and documentation were used as the basis for inductive analysis. The results of the study indicate that new voters have a good understanding of the importance of participating in elections and are actively seeking information, especially through social media. However, the challenge of disinformation remains, which can influence voter decisions. This study is expected to provide insight into the behavior of new voters and contribute to the development of more effective election socialization strategies.